Transmisión oral y edición textual: El Cantar de mio Cid, de la experiencia práctica a la edición - Antoni Rossell (Atalaya)
There are a large number of editions of the Cantar de mio Cid (also known in English as The Song of the Cid), and their interpretations are also highly varied. Beginning with a practical perspective of orality and performance, this paper will reflect on the edition and the meter of the Hispanic epic. This will be carried out through a musical reconstruction of this epic poem and from the impact that a musical interpretation has on the text.